Analysis of a solar photovoltaic-assisted absorption refrigeration system for domestic air conditioning. Issue 6 (2nd May 2016) - Ganguly, A.; Basu, Dipankar N.
ABSTRACT: Theoretical model of a solar photovoltaic integrated water-Lithium bromide absorption system is presented for domestic air conditioning. Surplus electrical energy from photovoltaic modules is used for charging the battery, which is utilized during the periods of zero or insufficient solar radiation. Minimum solar area required for each month is calculated and October is identified as the month requiring the highest area of photovoltaic arrays for a constant cooling load of 3.5 kW. The integrated system is found to be capable of sufficient amount of surplus electrical energy generation during both summer and winter months, with a daily excess of about 815 Ah of electrical energy on average over a complete calendar year. Designed system is found to be economically viable, having an energy payback period of 2.7 years.